Does FeNO Predict Clinical Characteristics in Chronic Cough? - Sadeghi, Mahboobeh Haji (Lung, 2017)
PURPOSE: To evaluate whether exhaled nitric oxide measurement can facilitate in the assessment of chronic cough patients based on their airway inflammatory phenotype. METHODS: We have studied consecutive patients attending a specialist cough clinic. 30 patients with high FeNO (> 30 ppb) and 20 patients with low FeNO (< 20 ppb) were recruited. RESULTS: There was a significant correlation between FeNO, B-Eos and sputum eosinophil count (p < 0.001). The number of recorded coughs in 24 h and HARQ scores were significantly (p < 0.05) higher in patients with a low FeNO. In contrast to the high FeNO group (48%), the greater proportion of these patients were women (90%). LCQ scores were worse in the low FeNO group but it was not significant. CONCLUSION: A strong relationship between FeNO, blood eosinophils and sputum eosinophils confirming phenotypic identity was observed. Whether the observed gender disparity accounts for the different cough frequency characteristics is unknown.